ANALISIS MANAJEMEN LABA DI SEKITAR (SEBELUM, SAAT DAN SESUDAH) PENERBITAN OBLIGASI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK JAKARTA (BEJ) - Risa Watti (Journal of Management and Business, 2006)
The purpose of this research is to obtain the empirical evidence of the company which has already issued the obligation. Whether that such company issues the obligation manipulates its earnings (or conducting "the window dressing") in order to perform the financial report of the client (or the prospective obligation seller) seems more profitable and excellent. The data results front the research, taken from the company which issues the obligation and has been listed at Jakarta Stock Exchange (BEJ) or the company which is 'go public', by picking up the data during the obligation issuance, and also the period of time within two years before and after the issuance. Whether during that period of time, the financial report ofthet company is exactly appropriate or has been manipulated by the client.The data is analysed by using “normality test" (one sample kolmogorov smirnov) if the parameter'uses 'paired sample T-test ± > 0,005 and if non parameter uses whitney U ranks Wilcoxon rank sum W-test ± < 0,005. As a result, showing that not all companies which issue the obligation manipulate the earnings or make up their financial report. It has been proved, in this research there is no'management of earnings' before the obligation issuance as well as the changing profits after the issuance. Thus we conclude, there is no ‘management earning' during the obligation issuance. Therefore, the investor or the prospective investor is not necessarily anxious about theirfinancial report when is reported by the management side to Jakarta Stock Exchange (BEJ) due to the appropiateness of its financial report involving the earning management.